2018
DOI: 10.3746/pnf.2018.23.3.196
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Memory and Antioxidant Protective Effects of Raisin (Currant) in Aged Rats

Abstract: Diets rich in fruits and vegetables can prevent age-related diseases. This research was conducted to evaluate the effects of raisin consumption on the spatial memory and morphometric parameters of brain tissue in aging rats. Old rats (20 months of age) were divided into 2 groups: control and raisin, with 6 rats in each group. The raisin group received 6 g of raisins daily in addition to their food and water for 90 days. After treatments, all animals were evaluated by behavioral tests to assess spatial memory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Study outcomes revealed that treatment with raisin mediated an increase in spatial memory, thus implying a neuroprotective effect in animal models. Similarly, Ghorbanian et al [65] suggested that raisin consumption in aging rats conferred an increase in blood antioxidant levels and enhanced cognitive function, thus positively affecting spatial memory.…”
Section: Health Benefits Of Greek Dried Grapes (In Vitro In Vivo and Clinical Trial Studies)mentioning
confidence: 96%
See 1 more Smart Citation
“…Study outcomes revealed that treatment with raisin mediated an increase in spatial memory, thus implying a neuroprotective effect in animal models. Similarly, Ghorbanian et al [65] suggested that raisin consumption in aging rats conferred an increase in blood antioxidant levels and enhanced cognitive function, thus positively affecting spatial memory.…”
Section: Health Benefits Of Greek Dried Grapes (In Vitro In Vivo and Clinical Trial Studies)mentioning
confidence: 96%
“…and opportunistic pathogens were decreased (Klebsiella sp.) [62] Sun-dried black raisins (Maviz) Neuroprotective Animal study: 12 old rats, 6 g raisins per day for 90 days Spatial memory was improved and cognitive and motor function were promoted [65] Sun-dried black raisins Neuroprotective…”
Section: Health Benefits Of Greek Dried Grapes (In Vitro In Vivo and Clinical Trial Studies)mentioning
confidence: 99%
“…It is all started with the food we consume. Stated here in this book that eating 21 red raisins a day on an empty stomach can generates good memory -can refer to the research done by Ghorbanian et al (2018) regarding the spatial memory and antioxidant protective effects of raisin. Besides that, eating the incense plant with sugar and drinking honey also might help to boost the memory.…”
Section: Chapter 12: Strategy To Boost Memorymentioning
confidence: 99%